Double trouble: The importance of reporting chorionicity and amnionicity in twin pregnancy ultrasound reports. Issue 1 (9th December 2014) - Constantine, Sarah; Wilkinson, Chris
Summary An obstetric ultrasound report in a twin pregnancy that does not unambiguously determine chorionicity and amnionicity in the first trimester is substandard. This article will assist radiologists to understand the importance of reporting the chorionicity and amnionicity in all twin obstetric scans.